Job Satisfaction as a Mediator of the Effect of Compensation and Leadership on Employee Performance - Azizatul Furqoniyah, Nur; Hadiyati, Ernani; Orbaningsih, Dwi (Enrichment: Journal of Multidisciplinary Research and Development, 2024)
Employee performance is an important factor in achieving organizational goals. Compensation and leadership are the two main variables that affect job satisfaction and employee performance. This study was conducted to explore the role of job satisfaction as a mediator in the relationship between compensation, leadership, and employee performance in the Notary & PPAT Office in Mojokerto Regency. This study aims to test and analyze the effects: 1) compensation on job satisfaction, 2) leadership on job satisfaction, 3) compensation on employee performance, 4) leadership on employee performance, 5) job satisfaction on employee performance, 6) compensation on employee performance through job satisfaction, and 7) leadership on employee performance through job satisfaction. This research uses an explanatory research approach and was conducted at the Notary & PPAT Office in Mojokerto Regency in February-May 2021. The population of the study was 45 employees (excluding leaders). The sample was determined using the saturated sample technique, which resulted in a sample of 45 people (excluding the leader). The results of the study prove that: 1) compensation affects job satisfaction, 2) leadership affects job satisfaction, 3) compensation affects employee performance, 4) leadership affects employee performance, 5) job satisfaction affects employee performance, 6) compensation affects employee performance through job satisfaction, and 7) leadership affects employee performance through job satisfaction. This study implies that to improve employee performance in the Notary & PPAT Office in Mojokerto Regency, the focus needs to be given to improving job satisfaction through improving compensation and leadership.